Cascade Regioselective Heterocyclization of 2-Acyl-1,1,3,3-tetracyanopropenides: Synthesis of Pyrrolo[3,4-c]pyridine and Pyrrolo[3,4-d]thieno[2,3-b]pyridine Derivatives - Grigor’ev, Arthur A.; Karpov, Sergey V.; Kayukov, Yakov S.; Gracheva, Iuliia A.; Tafeenko, Victor A. (Synlett, 2017)
2-Acyl-1,1,3,3-tetracyanopropenides (ATCN) undergo cascade heterocyclization under the action of aliphatic thiols, resulting in the formation of 6-(alkylthio)-4-amino-1-aryl(alkyl)-1-hydroxy-3-oxo-2,3-dihydro-1H-pyrrolo[3,4-c]pyridine-7-carbonitriles. The involvement of methyl mercaptoacetate to this reaction leads to the formation of the methyl 4,8-diamino-1-aryl-1-hydroxy-3-oxo-2,3-dihydro-1H-pyrrolo[3,4-d]thieno[2,3-b]pyridine-7-carboxylates, containing a new fused heterocyclic scaffold.
Keywords: tetracyanopropenide; heterocyclization; fused heterocycles